Association between NAT2 polymorphisms and the risk of schizophrenia in a Northern Chinese Han population. (April 2017) - Luan, Zhilin; Lu, Tianlan; Yue, Weihua; Copray, Sjef; Zhang, Dai
Abstract : The gene that encodes N -acetyltransferase 2 ( NAT2 ), an enzyme that plays a crucial role in the metabolism of many drugs and xenobiotics, is located on chromosome 8p22, one of the most convictive susceptibility loci of schizophrenia. NAT2 genetic polymorphisms lead to various enzyme acetylation phenotypes. In the present study, six selected NAT2 exonic single nucleotide polymorphisms were genotyped in an independent case–control sample of a Northern Chinese Han population to verify the possible association between NAT2 and schizophrenia. Three (rs1801280T/341C, rs1799930/G590A, and rs1208/A803G) of the six single nucleotide polymorphisms showed significant allele frequency differences between the case and the control groups after rigorous Bonferroni correction. One protective fast-acetylation haplotype ( NAT2*4 ) and two risk slow acetylation haplotypes ( NAT2*5B and NAT2*6A ) were discovered to be associated with schizophrenia. Our results indicate that NAT2 may be a susceptibility gene for schizophrenia in this Chinese Han population, and the risk haplotypes might cause the impairment of NAT2 in metabolizing neurotoxic substances. Abstract : Supplemental Digital Content is available in the text.